When Disjunction looks like Conjunction: Pragmatic Consequences in ASL - Davidson, Kathryn (Proceedings of the Amsterdam Colloquium, 2011)
In American Sign Language (ASL), conjunction and disjunction are often conveyed by the same coordinators (transcribed as "COORD"). So the sequence of signs WANT TEA COORD COFFEE can be interpreted as "I want tea or coffee" or "I want tea and coffee" depending on contextual or world knowledge or other linguistic information such as prosodic marking and the addition of disambiguating lexical material. In this paper I show that general use coordinators appearing in ASL can be a test case for understanding the role of the lexicalization of scalar items in the semantic/pragmatic phenomenon known as scalar implicature by collecting quantitative data from 10 adult native signers of ASL and 12 adult signers of English using a Felicity Judgment paradigm. Results show that there is a significant difference in interpretation of the general use coordination scale from other lexically-based scales in ASL and the lexically-based coordination scale in English, suggesting that lexical contrast between scalemates is important for scalar implicature calculation.